Evaluating the Financial Dynamics of Electric Vehicle Charging Stations in Thailand: Implications of Energy Cost Variability - Chiradeja, Pathomthat; Sottiyaphai, Chayanut; Ananwattanaporn, Santipont; Ngaopitakkul, Atthapol (My University, 2025)
This study examines the financial impact of energy costs on electric vehicle charging stations by comparing financial models with fixed and variable energy pricing structures. Through an in-depth financial simulation, key metrics such as Internal Rate of Return, Net Present Value, and payback period were calculated to evaluate the profitability and risk associated with each model. Findings reveal that charging stations with fixed energy costs generally experience a higher Internal Rate of Return at 14.55% and a Net Present Value of 1,711,781, with a payback period of four years. In comparison, stations with variable energy costs exhibit a lower Internal Rate of Return at 7.28% and a Net Present Value of 1,347,781, although the payback period remains consistent at four years. These results demonstrate that fixed energy costs enhance investment predictability and profitability, while variable costs increase exposure to energy price fluctuations, which raises financial risk but may capture greater returns under favorable market conditions. The analysis highlights the critical importance of accounting for energy cost variability in financial planning to maintain sustainable, profitable operations. This research provides essential insights for investors and policymakers to optimize electric vehicle charging infrastructure investments, supporting effective and profitable operations.
Keywords: Consumer preference; energy cost; EV charging; pricing